How I see it: An exploratory study on attributions and emotions in L2 learning - Nakamura, Sachiko (Studies in Second Language Learning and Teaching, 2018)
Learners’ attributions have received increasing attention in second/foreign language (L2) learning. Studies have shown that how learners attribute their performance influences not only their self-efficacy, motivation, and goal attainment but also their emotions (Hsieh, 2012; Hsieh & Kang, 2010; Hsieh & Shallert, 2008; Weiner, 2000, 2014). This exploratory study investigated how Japanese adult learners of L2 English attributed changes in their L2 learning attitudes and motivation through a 10-week TOEIC preparation program. It also examined emotions expressed in their attributional statements and the differences between learners with lower and higher L2 proficiency. A content analysis of open-ended questionnaire responses suggested eight attributional categories: perceived L2 improvement, enjoyment, positive feelings, increased L2 exposure, realization of L2 needs and importance, effective L2 instruction, and praise from the teacher for positive changes in attitudes and/or motivation and perceived inefficient L2 skills for negative changes in attitudes and/or motivation. Enjoyment was an emotion the most frequently mentioned by both groups while other emotions, such as joy, happiness, and disappointment, were expressed only by the beginner learners. These results offer important implications for L2 pedagogy and prospects for further research in the area.